Ailanthus altissima (Miller) Swingle fruit - new acyl β -sitosteryl glucoside and in vitro pharmacological evaluation - Sohail Khan; Aftab Hussain; Ansar Mehmood; Rashad Mehmood; Shagufta Perveen; Muhammad Imran (Natural Product Research, 2016)

Influence of Metal-Resistant Rhizobacteria on the Growth of Helianthus annuus L. in Cr(VI)-Contaminated Soil - Ali Bahadur; Aftab Afzal; Rizwan Ahmad; Fahad Nasir; Aman Khan; Vishandas Suthar; Gul Jan; Asfa Batool; Muhammad Amir Zia; Muhammad Mahmood-ul-Hassan (Water, Air, & Soil Pollution, 2016)

Serological, molecular detection and potential risk factors associated with camel brucellosis in Pakistan - Sana Fatima; Iahtasham Khan; Amar Nasir; Muhammad Younus; Muhammad Saqib; Falk Melzer; Heinrich Neubauer; Hosny El-Adawy (Tropical Animal Health and Production, 2016)

Molecular Dynamics Simulation of Transport and Separation of Carbon Dioxide–Alkane Mixtures in a Nanoporous Membrane Under Sub- and Supercritical Conditions - Mahnaz Firouzi; Muhammad Sahimi (Transport in Porous Media, 2016)

Bioaccumulation of heavy metals and analysis of mineral element alongside proximate composition in foot, gills and mantle of freshwater mussels (Anodonta anatina) - Muhammad Sohail; Muhammad Naeem Khan; Abdul Shakoor Chaudhry; Naureen Aziz Qureshi (Rendiconti Lincei. Scienze Fisiche e Naturali, 2016)

Modelling the kinetics of hexavalent molybdenum (Mo6+) reduction by the Serratia sp. strain MIE2 in batch culture - Mohd Izuan Effendi Halmi; Siti Rozaimah Sheikh Abdullah; Wan Lutfi Wan Johari; Mohd Shukuri Muhammad Ali; Noor Azmi Shaharuddin; Ariff Khalid; Mohd Yunus Shukor (Rendiconti Lincei. Scienze Fisiche e Naturali, 2016)

Screening of Potato Cultivars to Potato Mop-Top Virus in Northwestern Pakistan - Muhammad Arif; Ghazala Ruby; Anayatur Rehman; Murad Ali; Shamsur Rehman (Potato Research, 2016)

Improving magnesium uptake, photosynthesis and antioxidant enzyme activities of watermelon by grafting onto pumpkin rootstock under low magnesium - Yuan Huang; Yanyan Jiao; Muhammad Azher Nawaz; Chen Chen; Li Liu; Zhen Lu; Qiusheng Kong; Fei Cheng; Zhilong Bie (Plant and Soil, 2016)

Vulnerability of flash flooding in Riyadh, Saudi Arabia - Muhammad Tauhidur Rahman; Adel S. Aldosary; Kh Md Nahiduzzaman; Imran Reza (Natural Hazards, 2016)

Spatial distribution of natural γ radiation exposure and its relationship to soil types - Ahmad Termizi Ramli; Mohammad Syazwan Mohd Sanusi; Muhammad Hisyam Lee; Sallehuddin Sahrone; Nor Zati Hani Abu Hanifah (Natural Hazards, 2016)

An Investigation of the Innate Immune Response in Bovine Mammary Epithelial Cells Challenged by Prototheca zopfii - Zhaoju Deng; Muhammad Shahid; Limei Zhang; Jian Gao; Xiaolong Gu; Shiyao Zhang; Jiaqi Zou; Séamus Fanning; Bo Han (Mycopathologia, 2016)

AGEs/sRAGE, a novel risk factor in the pathogenesis of end-stage renal disease - Kailash Prasad; Indu Dhar; Qifeng Zhou; Hamdi Elmoselhi; Muhammad Shoker; Ahmed Shoker (Molecular and Cellular Biochemistry, 2016)

Synthesis, biological activities and docking studies of novel 2,4-dihydroxybenzaldehyde based Schiff base - Shahzad Murtaza; Aadil Abbas; Kiran Iftikhar; Saima Shamim; Muhammad Shoaib Akhtar; Zobia Razzaq; Khadija Naseem; Abdallah Mohamed Elgorban (Medicinal Chemistry Research, 2016)

Functional Analysis of VvBG1 During Fruit Development and Ripening of Grape - Haifeng Jia; Chen Wang; Cheng Zhang; Muhammad Salman Haider; Pengcheng Zhao; Zhongjie Liu; Lingfei Shangguan; Tariq Pervaiz; Jinggui Fang (Journal of Plant Growth Regulation, 2016)

Numerical simulation of the impacts of reflected tsunami waves on Pulo Raya Island during the 2004 Indian Ocean tsunami - Teuku Muhammad Rasyif; Syamsidik; Musa Al’ala; Mirza Fahmi (Journal of Coastal Conservation, 2016)

Computational Analysis and Binding Site Identification of Type III Secretion System ATPase from Pseudomonas aeruginosa - Raju Dash; S. M. Zahid Hosen; Tasniha Sultana; Md. Junaid; Mohuya Majumder; Ismat Ara Ishat; Mir Muhammad Nasir Uddin (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Evaluation of Phytophthora root rot- and bacterial wilt-resistant inbred lines and their crosses for use as rootstocks in pepper (Capsicum annuum L.) - Alebel Mekuriaw Abebe; Khin Pa Pa Wai; Muhammad Irfan Siddique; Hwang-Sung Mo; Hee Ju Yoo; Yoonhyuk Jegal; Si-Eun Byeon; Kil-Su Jang; Su-Gyeong Jeon; Ji-Eun Hwang; Byung-Soo Kim (Horticulture, Environment, and Biotechnology, 2016)

Haematology and blood chemistry references values for clinically healthy red-wattled lapwing (Vanellus indicus) - Sajid Umar; Kiran Aqil; Rizwan Qayyum; Muhammad Younus; Qamar-un-Nisa; Shahzad Ali; Muhammad Ali Shah; Muhammad Irfan; Muhammad Usman; Asif Ali; Akbar Ali; Adnan Ayan; et al. (European Journal of Wildlife Research, 2016)

Electrochemical impedance spectroscopy for black lipid membranes fused with channel protein supported on solid-state nanopore - Muhammad S. Khan; Noura S. Dosoky; Bakhrom K. Berdiev; John D. Williams (European Biophysics Journal, 2016)

Vortex-assisted ionic liquid-based dispersive liquid–liquid microextraction for assessment of chromium species in artificial saliva extract of different chewing tobacco products - Asma Akhtar; Tasneem Gul Kazi; Hassan Imran Afridi; Syed Ghulam Musharraf; Farah Naz Talpur; Noman Khan; Muhammad Bilal; Mustafa Khan (Environmental Science and Pollution Research, 2016)

Tourism in Austria: biodiversity, environmental sustainability, and growth issues - Muhammad Asad Saleem Malik; Syed Asim Shah; Khalid Zaman (Environmental Science and Pollution Research, 2016)

Oxidative stress responses in Wistar rats on subacute exposure to pharmaceutical wastewater - Ali Sharif; Muhammad Ashraf; Aqeel Javeed; Aftab Ahmed Anjum; Muhammad Furqan Akhtar; Bushra Akhtar; Ammara Saleem (Environmental Science and Pollution Research, 2016)

Ameliorative effect of synthetic γ-aminobutyric acid (GABA) on performance traits, antioxidant status and immune response in broiler exposed to cyclic heat stress - Naila Chand; Sher Muhammad; Rifat Ullah Khan; Ibrahim Abdullah Alhidary; Zia ur Rehman (Environmental Science and Pollution Research, 2016)

Measurement of metal bioaccessibility in vegetables to improve human exposure assessments: field study of soil–plant–atmosphere transfers in urban areas, South China - TianTian Xiong; Camille Dumat; Antoine Pierart; Muhammad Shahid; Yuan Kang; Ning Li; Georges Bertoni; Christophe Laplanche (Environmental Geochemistry and Health, 2016)

System dynamic modeling of CO2 emissions and pollutants from passenger cars in Malaysia, 2040 - Muhammad Azmi; Akihiro Tokai (Environment Systems and Decisions, 2016)

Relationship between land use composition and PM10 concentrations in Iskandar Malaysia - Muhammad Azahar Zikri Zahari; M. Rafee Majid; Chin Siong Ho; Gakuji Kurata; Nordin Nadhirah; Safitri Zen Irina (Clean Technologies and Environmental Policy, 2016)

Characterization of nanocellulose recovery from Elaeis guineensis frond for sustainable development - Muhammad Safwan Mohaiyiddin; Ong Hui Lin; Wei Tieng Owi; Chi Hoong Chan; Chin Hua Chia; Sarani Zakaria; Al Rey Villagracia; Hazizan Md Akil (Clean Technologies and Environmental Policy, 2016)

Effects of Organic Selenium Supplementation on Growth, Accumulation, Haematology and Histopathology of Juvenile Barramundi (Lates calcarifer) Fed High Soybean Meal Diets - Ilham Ilham; Muhammad Abu Bakar Siddik; Ravi Fotedar (Biological Trace Element Research, 2016)

Studies on genetics, stability and possible mechanism of deltamethrin resistance in Phenacoccus solenopsis Tinsley (Homoptera: Pseudococcidae) from Pakistan - BUSHRA SADDIQ; MUHAMMAD BABAR SHAHZAD AFZAL; SARFRAZ ALI SHAD (Journal of Genetics, 2016)

Dietary mycotoxins binders: a strategy to reduce aflatoxin m1 residues and improve milk quality of lactating Beetal goats - Haq Aman Ullah; Aneela Zameer Durrani; Muhammad Ijaz; Aqeel Javeed; Umer Sadique; Zahoor Ul Hassan; Altaf Ur Rahman; Muqader Shah; Irfan Khattak (Journal of Consumer Protection and Food Safety, 2016)

Metamorphic temperature investigation of coexisting calcite and dolomite marble––examples from Nikani Ghar marble and Nowshera Formation, Peshawar Basin, Pakistan - Muhammad Fahad; Yaseen Iqbal; Mohammad Riaz; Rick Ubic; Simon A. T. Redfern (Journal of Earth Science, 2016)

Tectonic study of the Sub-Himalayas based on geophysical data in Azad Jammu and Kashmir and northern Pakistan - Muhammad Rustam Khan; Fahad Hameed; Muhammad Saleem Mughal; Muhammad Basharat; Sohail Mustafa (Journal of Earth Science, 2016)

Erratum to: An application of rock physics modeling to quantify the seismic response of gas hydrate-bearing sediments in Makran accretionary prism, offshore, Pakistan - Muhammad Irfan Ehsan; Nisar Ahmed; Perveiz Khalid; Liu Xue Wei; Mustansar Naeem (Geosciences Journal, 2016)

Genome-wide characterization and expression pattern of auxin response factor (ARF) gene family in soybean and common bean - Bao Le; Muhammad Amjad Nawaz; Hafiz Mamoon Rehman; Thu Le; Seung Hwan Yang; Kirill S. Golokhvast; Eunho Son; Gyuhwa Chung (Genes & Genomics, 2016)

TK1656, an L-asparaginase from Thermococcus kodakarensis, a novel candidate for therapeutic applications - Shahid Mahmood Chohan; Muhammad Atif Nisar; Naeem Rashid; Ghazaleh Gharib; Qamar Bashir; Masood Ahmed Siddiqui (Biologia, 2016)

Plant growth promoting rhizobacteria suppress blast disease caused by Pyricularia oryzae and increase grain yield of rice - Afroz Rais; Muhammad Shakeel; Fauzia Yusuf Hafeez; Muhammad Nadeem Hassan (BioControl, 2016)

The combined treatment of Mn and Al alleviates the toxicity of Al or Mn stress alone in barley - Noor Muhammad; Shengguan Cai; Jawad Munawar Shah; Guoping Zhang (Acta Physiologiae Plantarum, 2016)

An application of AVO derived attributes to analyze seismic anomalies of gas hydrate bearing sediments in Makran offshore, Pakistan - Muhammad Irfan Ehsan; Nisar Ahmed; Zia Ud Din; Perveiz Khalid; Liu Xue Wei (Acta Geodaetica et Geophysica, 2016)

Antileishmanial diterpenoid alkaloids from Aconitum spicatum (Bruhl) Stapf - Sajan L. Shyaula; Tensangmu Tamang; Nida Ghouri; Achyut Adhikari; Shanti Marasini; Gan B. Bajracharya; Mangala D. Manandhar; Muhammad Iqbal Choudhary (Natural Product Research, 2016)

Assessing tropical cyclone impacts using object-based moderate spatial resolution image analysis: a case study in Bangladesh - Muhammad Al-Amin Hoque; Stuart Phinn; Chris Roelfsema; Iraphne Childs (International Journal of Remote Sensing, 2016)

Characterization of a salt resistant bacterial strain Proteus sp. NA6 capable of decolorizing reactive dyes in presence of multi-metal stress - Naila Abbas; Sabir Hussain; Farrukh Azeem; Tanvir Shahzad; Sajjad Haider Bhatti; Muhammad Imran; Zulfiqar Ahmad; Zahid Maqbool; Muhammad Abid (World Journal of Microbiology and Biotechnology, 2016)

Assessment of Toxic Metal Uptake by Different Vegetables Grown on Soils Amended with Poultry Waste: Risk Assessment - Oan Muhammad Sahito; Tasneem Gul Kazi; Hassan Imran Afridi; Jameel Ahmed Baig; Farah Naz Talpur; Shahnawaz Baloch; Nusrat Shahab Memon; Nasreen Gul Kori (Water, Air, & Soil Pollution, 2016)

Salt-stress-responsive chloroplast proteins in Brassica juncea genotypes with contrasting salt tolerance and their quantitative PCR analysis - Peerzada Yasir Yousuf; Altaf Ahmad; Ibrahim M. Aref; Munir Ozturk; Hemant; Arshid Hussain Ganie; Muhammad Iqbal (Protoplasma, 2016)

Drought monitoring and performance evaluation of MODIS-based drought severity index (DSI) over Pakistan - Muhammad Athar Haroon; Jiahua Zhang; Fengmei Yao (Natural Hazards, 2016)

Cotton production under risk: a simultaneous adoption of risk coping tools - Farhad Zulfiqar; Raza Ullah; Muhammad Abid; Abid Hussain (Natural Hazards, 2016)

Synthesis and urease inhibitory activities of benzophenone semicarbazones/thiosemicarbazones - Arshia Arshia; Ajmal Khan; Khalid Mohammed Khan; Syed Muhammad Saad; Nida Iqbal Siddiqui; Sumaira Javaid; Shahnaz Perveen; M. Iqbal Choudhary (Medicinal Chemistry Research, 2016)

Comparative enzyme inhibition study of 1-deazapurines - Iftikhar Ali; Ajmal Khan; Amjad Hussain; Umar Farooq; Muhammad Ismail; Viqar Hyder; Viqar U. Ahmad; Viktor O. Iaroshenko; Hidayat Hussain; Peter Langer (Medicinal Chemistry Research, 2016)

Multichromic Bis-Axially Extended Perylene Chromophore with Schiff Bases: Synthesis, Characterization and Electrochemical Studies - Ghulam Shabir; Aamer Saeed; Muhammad Arshad; Muhammad Zahid (Journal of Fluorescence, 2016)

Mutation in SLC6A9 encoding a glycine transporter causes a novel form of non-ketotic hyperglycinemia in humans - Majid Alfadhel; Marwan Nashabat; Hanan Al Qahtani; Ahmed Alfares; Fuad Al Mutairi; Hesham Al Shaalan; Ganka V. Douglas; Klaas Wierenga; Jane Juusola; Muhammad Talal Alrifai; Stefan T. Arold; Fowzan Alkuraya; et al. (Human Genetics, 2016)

Analysis of geological structure and anthropological factors affecting arsenic distribution in the Lahore aquifer, Pakistan - Akhtar Malik Muhammad; Tang Zhonghua; Zakari Sissou; Bahaa Mohamadi; Muhsan Ehsan (Hydrogeology Journal, 2016)

Prediction of pore-water pressure response to rainfall using support vector regression - Nuraddeen Muhammad Babangida; Muhammad Raza Ul Mustafa; Khamaruzaman Wan Yusuf; Mohamed Hasnain Isa (Hydrogeology Journal, 2016)

Individual and combined effects of crude protein, methionine, and probiotic levels on laying hen productive performance and nitrogen pollution in the manure - Mahmoud Alagawany; Mohamed E. Abd El-Hack; Muhammad Arif; Elwy A. Ashour (Environmental Science and Pollution Research, 2016)

Bioavailability evaluation, uptake of heavy metals and potential health risks via dietary exposure in urban-industrial areas - Balal Yousaf; Guijian Liu; Ruwei Wang; Muhammad Imtiaz; Muhammad Zia-ur-Rehman; Mehr Ahmed Mujtaba Munir; Zhiyuan Niu (Environmental Science and Pollution Research, 2016)

Biochar enhances the cadmium tolerance in spinach (Spinacia oleracea) through modification of Cd uptake and physiological and biochemical attributes - Uzma Younis; Saeed Ahmad Malik; Muhammad Rizwan; Muhammad Farooq Qayyum; Yong Sik Ok; Muhammad Hasnain Raza Shah; Rabia Abdur Rehman; Niaz Ahmad (Environmental Science and Pollution Research, 2016)

Computing soil creep velocity using dendrochronology - Mohammad Amjad Sabir; Muhammad Umar; Muhammad Farooq; Faridullah Faridullah (Bulletin of Engineering Geology and the Environment, 2016)

Pcal_1127, a highly stable and efficient ribose-5-phosphate pyrophosphokinase from Pyrobaculum calidifontis - Tahira Bibi; Sumera Perveen; Iram Aziz; Qamar Bashir; Naeem Rashid; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2016)

Protein profiling analysis of Gossypium hirsutum (Malvales: Malvaceae) leaves infested by cotton whitefly Bemisia tabaci (Homoptera: Aleyrodidae) - Muhammad Ibrahim; Sumaira Yasmeen; Ghanva Zaman; Li Bin; Fahad Al-Qurainy; Habib-ur-Rehman Athar; Kausar Hussain Shah; Muhammad Khurshid; Muhammad Ashraf (Applied Entomology and Zoology, 2016)

Physiological and biochemical mechanisms of silicon-induced copper stress tolerance in cotton (Gossypium hirsutum L.) - Shafaqat Ali; Muhammad Rizwan; Najeeb Ullah; Saima Aslam Bharwana; Muhammad Waseem; Muhammad Ahsan Farooq; Ghulam Hasan Abbasi; Mujahid Farid (Acta Physiologiae Plantarum, 2016)

Atmospheric emission of nitric oxide and processes involved in its biogeochemical transformation in terrestrial environment - Awais Shakoor; Muhammad Abdullah; Balal Yousaf; Amina; Youhua Ma (Environmental Science and Pollution Research, 2016)

A new fatty acid ester from an edible mushroom Rhizopogon luteolus - Gülsen Tel-Çayan; Akhtar Muhammad; Mehmet Emin Duru; Mehmet Öztürk; Achyut Adhikari; Aziz Türkoğlu (Natural Product Research, 2016)

Recent Climate Trends and Drought Behavioral Assessment Based on Precipitation and Temperature Data Series in the Songhua River Basin of China - Muhammad Imran Khan; Dong Liu; Qiang Fu; Shuhua Dong; Umar Waqas Liaqat; Muhammad Abrar Faiz; Yuxiang Hu; Qaisar Saddique (Water Resources Management, 2016)

Modulation of antioxidant enzymes in Juniperus procera needles in relation to habitat environment and dieback incidence - Ibrahim M. Aref; Pervaiz R. Khan; Salim Khan; Hashim El-Atta; Abdalla I. Ahmed; Muhammad Iqbal (Trees, 2016)

Biotransformation of Tetrahydrocannabinol - Muhammad T. Akhtar; Khozirah Shaari; Robert Verpoorte (Phytochemistry Reviews, 2016)

Dynamic linkages among energy consumption, air pollution, greenhouse gas emissions and agricultural production in Pakistan: sustainable agriculture key to policy success - Muhammad Imran Qureshi; Usama Awan; Zeeshan Arshad; Amran Md. Rasli; Khalid Zaman; Faisal Khan (Natural Hazards, 2016)

Investigation of novel LPS-induced differentially expressed long non-coding RNAs in endothelial cells - Krishna K. Singh; Pratiek N. Matkar; Shoaib Muhammad; Adrian Quan; Vijay Gupta; Hwee Teoh; Mohammed Al-Omran; Subodh Verma (Molecular and Cellular Biochemistry, 2016)

Cirrhotic patients have good insight into their daily functional impairment despite prior hepatic encephalopathy: comparison with PROMIS norms - Jasmohan S. Bajaj; Melanie B. White; Ariel B. Unser; Dinesh Ganapathy; Andrew Fagan; Edith A. Gavis; Richard K. Sterling; Douglas M. Heuman; Scott Matherly; Puneet Puri; Arun J. Sanyal; Velimir Luketic; et al. (Metabolic Brain Disease, 2016)

Therapeutic potential of compound K as an IKK inhibitor with implications for osteoarthritis prevention: an in silico and in vitro study - Sera Kang; Muhammad Hanif Siddiqi; Sung Joo Yoon; Sungeun Ahn; Hae-Yong Noh; Natarajan Sathish Kumar; Yeon-Ju Kim; Deok-Chun Yang (In Vitro Cellular & Developmental Biology - Animal, 2016)

Effect of reduced oxygen concentration on the germination behavior of vegetable seeds - Muhammad Yasin; Christian Andreasen (Horticulture, Environment, and Biotechnology, 2016)

Genetic diversity analysis of Pakistan rice (Oryza sativa) germplasm using multiplexed single nucleotide polymorphism markers - Shahid Masood Shah; Muhammad Arif; Kashif Aslam; Ghulam Shabir; Michael J. Thomson (Genetic Resources and Crop Evolution, 2016)

Carnivores’ diversity and conflicts with humans in Musk Deer National Park, Azad Jammu and Kashmir, Pakistan - Shakeel Ahmad; Shoaib Hameed; Hussain Ali; Tauheed Ullah Khan; Tahir Mehmood; Muhammad Ali Nawaz (European Journal of Wildlife Research, 2016)

Toxicity and oxidative stress induced by chromium in workers exposed from different occupational settings around the globe: A review - Muhammad Junaid; Muhammad Zaffar Hashmi; Riffat Naseem Malik; De-Sheng Pei (Environmental Science and Pollution Research, 2016)

The impact of seasonal variation on organochlorine pesticide residues in buffalo and cow milk of selected dairy farms from Faisalabad region - Muhammad Wasim Sajid; Muhammad Shamoon; Muhammad Atif Randhawa; Muhammad Asim; Abdul Shakoor Chaudhry (Environmental Monitoring and Assessment, 2016)

Role of exogenous salicylic acid in regulating physio-morphic and molecular changes under chromium toxicity in black- and yellow- seeded Brassica napus L. - Rafaqat A. Gill; Na Zhang; Basharat Ali; Muhammad A. Farooq; Jianxiang Xu; Muhammad B. Gill; Bizeng Mao; Weijun Zhou (Environmental Science and Pollution Research, 2016)

Comparison of antioxidant enzyme activities and DNA damage in chickpea (Cicer arietinum L.) genotypes exposed to vanadium - Muhammad Imtiaz; Muhammad Adnan Mushtaq; Muhammad Shahid Rizwan; Muhammad Saleem Arif; Balal Yousaf; Muhammad Ashraf; Xiong Shuanglian; Muhammad Rizwan; Sajid Mehmood; Shuxin Tu (Environmental Science and Pollution Research, 2016)

Photocatalytic CO2 conversion over Au/TiO2 nanostructures for dynamic production of clean fuels in a monolith photoreactor - Beenish Tahir; Muhammad Tahir; Nor Aishah Saidina Amin (Clean Technologies and Environmental Policy, 2016)

Particulate composites based on ionic liquid-treated oil palm fiber and thermoplastic starch adhesive - Hamayoun Mahmood; Muhammad Moniruzzaman; Suzana Yusup; Hazizan Md. Akil (Clean Technologies and Environmental Policy, 2016)

RETRACTED ARTICLE: Toxic Effects of Titanium Dioxide Nanoparticles and Titanium Dioxide Bulk Salt in the Liver and Blood of Male Sprague-Dawley Rats Assessed by Different Assays - Muhammad Shakeel; Farhat Jabeen; Naureen Aziz Qureshi; Muhammad Fakhr-e-Alam (Biological Trace Element Research, 2016)

The 35-amino acid C2 protein of Cotton leaf curl Kokhran virus, Burewala, implicated in resistance breaking in cotton, retains some activities of the full-length protein - Fazal Akbar; Zafar Iqbal; Rob W. Briddon; Franck Vazquez; Muhammad Saeed (Virus Genes, 2016)

Role of Leptin Deficiency, Inefficiency, and Leptin Receptors in Obesity - Muhammad Wasim; Fazli Rabbi Awan; Syeda Sadia Najam; Abdul Rehman Khan; Haq Nawaz Khan (Biochemical Genetics, 2016)

Comparison of the immunogenicity of two inactivated recombinant rabies viruses overexpressing the glycoprotein - Muhammad Tariq Navid; Yingying Li; Ming Zhou; Min Cui; Zhen F. Fu; Lijun Tang; Ling Zhao (Archives of Virology, 2016)

Sphingomonas hankyongensis sp. nov. isolated from tap water - Sung-Sik Yun; Muhammad Zubair Siddiqi; Soon-Youl Lee; Minseok S. Kim; KangDuk Choi; Wan-Taek Im (Archives of Microbiology, 2016)

Zinc seed coating improves the growth, grain yield and grain biofortification of bread wheat - Abdul Rehman; Muhammad Farooq (Acta Physiologiae Plantarum, 2016)

Phytomanagement of heavy metals in contaminated soils using sunflower: A review - Muhammad Rizwan; Shafaqat Ali; Hina Rizvi; Jörg Rinklebe; Daniel C. W. Tsang; Erik Meers; Yong Sik Ok; Wajid Ishaque (Critical Reviews in Environmental Science and Technology, 2016)

An Exploration of Wind Stress Calculation Techniques in Hurricane Storm Surge Modeling - Kyra Bryant; Muhammad Akbar (Journal of Marine Science and Engineering, 2016)
As hurricanes continue to threaten coastal communities, accurate storm surge forecasting remains a global priority. Achieving a reliable storm surge prediction necessitates accurate hurricane intensity and wind field information. The wind field must be converted to wind stress, which represents the air-sea momentum flux component required in storm surge and other oceanic models. This conversion requires a multiplicative drag coefficient for the air density and wind speed to represent the air-sea momentum exchange at a given location. Air density is a known parameter and wind speed is a forecasted variable, whereas the drag coefficient is calculated using an empirical correlation. The correlation’s accuracy has brewed a controversy of its own for more than half a century. This review paper examines the lineage of drag coefficient correlations and their acceptance among scientists.

Aluminum and Chromium Toxicity in Maize: Implications for Agronomic Attributes, Net Photosynthesis, Physio-Biochemical Oscillations, and Metal Accumulation in Different Plant Parts - Shakeel Ahmad Anjum; Umair Ashraf; Imran Khan; Mohsin Tanveer; Muhammad Farrukh Saleem; Longchang Wang (Water, Air, & Soil Pollution, 2016)

The Effect of Chelating Agents on Enhancement of 1,1,1-Trichloroethane and Trichloroethylene Degradation by Z-nZVI-Catalyzed Percarbonate Process - Muhammad Danish; Xiaogang Gu; Shuguang Lu; Xiang Zhang; Xiaori Fu; Yunfei Xue; Zhouwei Miao; Ayyaz Ahmad; Muhammad Naqvi; Abdul Sattar Qureshi (Water, Air, & Soil Pollution, 2016)

Multivariate Drought Assessment Considering the Antecedent Drought Conditions - Muhammad Waseem; Muhammad Ajmal; Joo Heon Lee; Tae-Woong Kim (Water Resources Management, 2016)

Isolation and characterization of genotype XIII Newcastle disease virus from Emu in India - Vasudevan Gowthaman; Sambhu Dayal Singh; Kuldeep Dhama; Perumal Aurumugam Desingu; Asok Kumar; Yashpal Singh Malik; Muhammad Munir (VirusDisease, 2016)

Comparative Study of Physical Factors and Microbial Diversity of Four Man-Made Extreme Ecosystems - Imran Ali; Ali Akbar; Muhammad Aslam; Sami Ullah; Muhammad Anwar; Hunsa Punnapayak; Pongtharin Lotrakul; Sehanat Prasongsuk; Benjawan Yanwisetpakdee; Ponlada Permpornsakul; Sudip K. Rakshit (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Response of Datura innoxia Linn. to Gamma Rays and Its Impact on Plant Growth and Productivity - Ibrahim M. Aref; Pervaiz R. Khan; Abdulaziz A. Al Sahli; Azamal Husen; M. K. A. Ansari; Mahmooduzzafar; Muhammad Iqbal (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Examination of CK2α and NF-κB p65 expression in human benign prostatic hyperplasia and prostate cancer tissues - Fatima Qaiser; Janeen H. Trembley; Sarah Sadiq; Iqbal Muhammad; Rubina Younis; Shoaib Naiyar Hashmi; Badar Murtaza; Thomas S. Rector; Abdul Khaliq Naveed; Khalil Ahmed (Molecular and Cellular Biochemistry, 2016)

Syntheses, in vitro evaluation and molecular docking studies of 5-bromo-2-aryl benzimidazoles as α-glucosidase inhibitors - Tanzila Arshad; Khalid Mohammed Khan; Najma Rasool; Uzma Salar; Shafqat Hussain; Tehreem Tahir; Mohammed Ashraf; Abdul Wadood; Muhammad Riaz; Shahnaz Perveen; Muhammad Taha; Nor Hadiani Ismail (Medicinal Chemistry Research, 2016)

Synthesis, in vitro potential and computational studies on 2-amino-1, 4-dihydropyrimidines as multitarget antibacterial ligands - Muhammad Jawad Ahmad; Syed Fahad Hassan; Riffat Un Nisa; Khurshid Ayub; Muhammad Shahid Nadeem; Samina Nazir; Farzana Latif Ansari; Naveeda Akhtar Qureshi; Umer Rashid (Medicinal Chemistry Research, 2016)

Early detection of the effects of compaction in forested soils: evidence from selective extraction techniques - Muhammad Farrakh Nawaz; Guilhem Bourrié; Fabienne Trolard; Jacques Ranger; Sadaf Gul; Nabeel Khan Niazi (Journal of Soils and Sediments, 2016)

Impact of flue gas desulfurization gypsum and lignite humic acid application on soil organic matter and physical properties of a saline-sodic farmland soil in Eastern China - Jiangkuan Nan; Xiaomin Chen; Can Chen; Muhammad Siddique Lashari; Jianqiang Deng; Zhenjie Du (Journal of Soils and Sediments, 2016)

The potential of precision surface irrigation in the Indus Basin Irrigation System - Arif A. Anwar; Waqas Ahmad; Muhammad Tousif Bhatti; Zia Ul Haq (Irrigation Science, 2016)

Modeling a weak turbulent flow in a narrow and wavy channel: case of micro-irrigation - Jafar Al-Muhammad; Séverine Tomas; Fabien Anselmet (Irrigation Science, 2016)

Longitudinal study of experimental induction of AA amyloidosis in mice seeded with homologous and heterologous AA fibrils - Naeem Muhammad; Tomoaki Murakami; Yasuo Inoshima; Naotaka Ishiguro (Inflammation Research, 2016)

Uptake and distribution of minerals and heavy metals in commonly grown leafy vegetable species irrigated with sewage water - Sumera Anwar; Muhammad Farrakh Nawaz; Sadaf Gul; Muhammad Rizwan; Shafaqat Ali; Arshaad Kareem (Environmental Monitoring and Assessment, 2016)

Effect of different amendments on rice (Oryza sativa L.) growth, yield, nutrient uptake and grain quality in Ni-contaminated soil - Pia Muhammad Adnan Ramzani; Waqas-ud-Din Khan; Muhammad Iqbal; Salma Kausar; Shafaqat Ali; Muhammad Rizwan; Zaheer Abbas Virk (Environmental Science and Pollution Research, 2016)

Influence of sub-lethal crude oil concentration on growth, water relations and photosynthetic capacity of maize (Zea mays L.) plants - Habib-ur-Rehman Athar; Sarah Ambreen; Muhammad Javed; Mehwish Hina; Sumaira Rasul; Zafar Ullah Zafar; Hamid Manzoor; Chukwuma C. Ogbaga; Muhammad Afzal; Fahad Al-Qurainy; Muhammad Ashraf (Environmental Science and Pollution Research, 2016)

Perspectives of using fungi as bioresource for bioremediation of pesticides in the environment: a critical review - Zahid Maqbool; Sabir Hussain; Muhammad Imran; Faisal Mahmood; Tanvir Shahzad; Zulfiqar Ahmed; Farrukh Azeem; Saima Muzammil (Environmental Science and Pollution Research, 2016)

Surfactant enhanced pyrene degradation in the rhizosphere of tall fescue (Festuca arundinacea) - Sardar Alam Cheema; Muhammad Imran Khan; Xianjin Tang; Chaofeng Shen; Muhammad Farooq; Yingxu Chen (Environmental Science and Pollution Research, 2016)

Evaluating levels and health risk of heavy metals in exposed workers from surgical instrument manufacturing industries of Sialkot, Pakistan - Muhammad Junaid; Muhammad Zaffar Hashmi; Riffat Naseem Malik (Environmental Science and Pollution Research, 2016)

Effect of UV-A radiation as an environmental stress on the development, longevity, and reproduction of the oriental armyworm, Mythimna separata (Lepidoptera: Noctuidae) - Arif Ali; Muhammad Adnan Rashid; Qiu Ying Huang; Chao-Liang Lei (Environmental Science and Pollution Research, 2016)

Cadmium stress in rice: toxic effects, tolerance mechanisms, and management: a critical review - Muhammad Rizwan; Shafaqat Ali; Muhammad Adrees; Hina Rizvi; Muhammad Zia-ur-Rehman; Fakhir Hannan; Muhammad Farooq Qayyum; Farhan Hafeez; Yong Sik Ok (Environmental Science and Pollution Research, 2016)

Drought tolerance potential of Vigna mungo L. lines as deciphered by modulated growth, antioxidant defense, and nutrient acquisition patterns - Qasim Ali; Muhammad Zulqurnain Haider; Wasif Iftikhar; Sidra Jamil; M. Tariq Javed; Ali Noman; Muhammad Iqbal; Rashida Perveen (Brazilian Journal of Botany, 2016)

Functional characterization of germin and germin-like protein genes in various plant species using transgenic approaches - Muhammad Ilyas; Awais Rasheed; Tariq Mahmood (Biotechnology Letters, 2016)

Arsenic Exposure in Children through Drinking Water in Different Districts of Sindh, Pakistan - Jameel Ahmed Baig; Tasneem Gul Kazi; Muhammad Ayaz Mustafa; Imam Bakhsh Solangi; Mirza Junaid Mughal; Hassan Imran Afridi (Biological Trace Element Research, 2016)

Erratum to: Pcal_0768, a hyperactive 4-α-glucanotransferase from Pyrobaculum calidifontis - Sumaira Mehboob; Nasir Ahmad; Naeem Rashid; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2016)

Analysis of the Appropriate Development Scale of Regional Paddy Field Under the Restriction of Water Resources - Dong Liu; Dan Zhao; Qiang Fu; Tianxiao Li; Muhammad Imran Khan; Wenting Liu; Faiz M. Abrar (Agricultural Research, 2016)

Hydroxylamine‐dependent anaerobic ammonium oxidation (anammox) by “ Candidatus Brocadia sinica” - Mamoru Oshiki; Muhammad Ali; Kaori Shinyako‐Hata; Hisashi Satoh; Satoshi Okabe (Environmental Microbiology, 2016)
Summary Although metabolic pathways and associated enzymes of anaerobic ammonium oxidation (anammox) of ‘ Ca . Kuenenia stuttgartiensis’ have been studied, those of other anammox bacteria are still poorly understood. reduction to NO is considered to be the first step in the anammox metabolism of ‘ Ca . K. stuttgartiensis’, however, ‘ Ca . Brocadia’ lacks the genes that encode canonical NO‐forming nitrite reductases (NirS or NirK) in its genome, which is different from ‘ Ca . K. stuttgartiensis’. Here, we studied the anammox metabolism of ‘ Ca . Brocadia sinica’. 15 N‐tracer experiments demonstrated that ‘ Ca . B. sinica’ cells could reduce to NH 2 OH, instead of NO, with as yet unidentified nitrite reductase(s). Furthermore, N 2 H 4 synthesis, downstream reaction of reduction, was investigated using a purified ‘ Ca . B. sinica' hydrazine synthase (Hzs) and intact cells. Both the ‘ Ca . B. sinica’ Hzs and cells utilized NH 2 OH and , but not NO and , for N 2 H 4 synthesis and further oxidized N 2 H 4 to N 2 gas. Taken together, the metabolic pathway of ‘ Ca . B. sinica’ is NH 2 OH‐dependent and different from the one of ‘ Ca . K. stuttgartiensis’, indicating metabolic diversity of anammox bacteria.

New lipoxygenase and cholinesterase inhibitory sphingolipids from Carthamus oxyacantha - Muhammad Dilshad; Naheed Riaz; Muhammad Saleem; Nusrat Shafiq; Muhammad Ashraf; Tayaba Ismail; Hafiza Mehwish Rafiq; Abdul Jabbar (Natural Product Research, 2016)

Antiviral phytochemicals identification from Azadirachta indica leaves against HCV NS3 protease: an in silico approach - Usman Ali Ashfaq; Asma Jalil; Muhammad Tahir ul Qamar (Natural Product Research, 2016)

Analysis and Design of Monopile Foundations for Offshore Wind-Turbine Structures - Muhammad Arshad; Brendan C. O'Kelly (Marine Georesources & Geotechnology, 2016)

Worldwide Status of Fresh Fruits Irradiation and Concerns about Quality, Safety, and Consumer Acceptance - Hafiz Muhammad Shahbaz; Kashif Akram; Jae-Jun Ahn; Joong-Ho Kwon (Critical Reviews in Food Science and Nutrition, 2016)

The Hilbert–Huang Transform-Based Denoising Method for the TEM Response of a PRBS Source Signal - Li Hai; Xue Guo-qiang; Zhao Pan; Zhong Hua-sen; Muhammad Younis Khan (Pure and Applied Geophysics, 2016)

Phytoremediation: recent advances in plant-endophytic synergistic interactions - Amna Ijaz; Asma Imran; Muhammad Anwar ul Haq; Qaiser M. Khan; Muhammad Afzal (Plant and Soil, 2016)

DNA Damage in Major Psychiatric Diseases - Muhammad Ummear Raza; Turan Tufan; Yan Wang; Christopher Hill; Meng-Yang Zhu (Neurotoxicity Research, 2016)

Rockfall susceptibility zoning based on back analysis of rockfall deposit inventory in Gunung Kelir, Java - Guruh Samodra; Guangqi Chen; Junun Sartohadi; Danang Sri Hadmoko; Kiyonobu Kasama; Muhammad Anggri Setiawan (Landslides, 2016)

Construction Materials from Stainless Steel Slags: Technical Aspects, Environmental Benefits, and Economic Opportunities - Muhammad Salman; Maarten Dubois; Andrea Di Maria; Karel Van Acker; Koenraad Van Balen (Journal of Industrial Ecology, 2016)
Summary State‐of‐the‐art technologies that implement theindustrial ecology concept only make it to the market if environmental gains and economic benefits are significant. Therefore, the article investigates, in an interdisciplinary way, two innovative technologies that valorize stainless steel (SS) slags as block masonry (bricks): carbonation and thermo‐alkali‐activation. The technical, environmental, and economic features of three SS bricks—solid bricks, perforated bricks, and lightweight aerated blocks—are compared to commercially available construction materials. Although the produced bricks meet industrial standards, technical challenges, such as optimization of alkali addition and use of metal molds, should be dealt with before upscaling to industrial production. A cradle‐to‐gate life cycle assessment that aggregates the results of the various impact categories shows that the environmental impact of solid and perforated SS bricks is lower than the impact of conventional clay‐baked bricks owing to the avoidance of additives for slag stabilization and energy consumption for sintering clay. The impact of aerated SS bricks was found to be similar to the commercially available aerated blocks. More specifically, the carbon dioxide uptake from carbonation reduces the overall environmental impact, whereas use of alkalis increases the impact. A strengths weaknesses opportunity threats analysis highlights the economic advantages of SS bricks originating from lower energy requirements, reduced dependence on primary resources, and improved metal recovery from slag. However, in order to apply the innovative technologies at industrial scale, challenges related to processing conditions, feedstock variability, and potential competition from existing brick suppliers have to be overcome.

Emission quantification of refrigerant CFCs, HCFCs and HFCs in megacity Lahore (Pakistan) and contributed ODPs and GWPs - Zia Ul-Haq; Muhammad Ali; Syeda Adila Batool; Salman Tariq; Zarmina Qayyum (Journal of Earth System Science, 2016)

Toxicity of nanoscale metal organic frameworks: a perspective - Muhammad Sajid (Environmental Science and Pollution Research, 2016)

Allelopathic potential of oil seed crops in production of crops: a review - Adnan Noor Shah; Javaid Iqbal; Abid Ullah; Guozheng Yang; Muhammad Yousaf; Shah Fahad; Mohsin Tanveer; Waseem Hassan; Shahbaz Atta Tung; Leishan Wang; Aziz Khan; Yingying Wu (Environmental Science and Pollution Research, 2016)

Chemical immobilization of Pb, Cu, and Cd by phosphate materials and calcium carbonate in contaminated soils - Guoyong Huang; Xiaojuan Su; Muhammad Shahid Rizwan; Yifei Zhu; Hongqing Hu (Environmental Science and Pollution Research, 2016)

Leaf-based physiological, metabolic, and ultrastructural changes in cultivated cotton cultivars under cadmium stress mediated by glutathione - M. K. Daud; Lei Mei; Azizullah Azizullah; Muhammad Dawood; Imran Ali; Qaisar Mahmood; Waheed Ullah; Muhammad Jamil; S. J. Zhu (Environmental Science and Pollution Research, 2016)

Immobilization of Pb and Cu in polluted soil by superphosphate, multi-walled carbon nanotube, rice straw and its derived biochar - Muhammad Shahid Rizwan; Muhammad Imtiaz; Guoyong Huang; Muhammad Afzal Chhajro; Yonghong Liu; Qingling Fu; Jun Zhu; Muhammad Ashraf; Mohsin Zafar; Saqib Bashir; Hongqing Hu (Environmental Science and Pollution Research, 2016)

First report on fish cysteine as a biomarker of contamination in the River Chenab, Pakistan - Bilal Hussain; Tayyaba Sultana; Salma Sultana; Shahid Mahboob; Muhammad Farooq; Khalid Al-Ghanim; Shahid Nadeem (Environmental Science and Pollution Research, 2016)

Simultaneously removal of inorganic arsenic species from stored rainwater in arsenic endemic area by leaves of Tecomella undulata: a multivariate study - Kapil Dev Brahman; Tasneem Gul Kazi; Hassan Imran Afridi; Jameel Ahmed Baig; Muhammad Ishaque Abro; Sadaf Sadia Arain; Jamshed Ali; Sumaira Khan (Environmental Science and Pollution Research, 2016)

Interrelationships between deformation and metamorphic events across the western hinterland zone, NW Pakistan - Asghar Ali; Mustafa Yar; Muhammad Asif Khan; Shah Faisal (Journal of Earth Science, 2016)

Mother-male bond, but not paternity, influences male-infant affiliation in wild crested macaques - Daphne Kerhoas; Lars Kulik; Dyah Perwitasari-Farajallah; Muhammad Agil; Antje Engelhardt; Anja Widdig (Behavioral Ecology and Sociobiology, 2016)

Lysobacter pocheonensis sp. nov., isolated from soil of a ginseng field - Muhammad Zubair Siddiqi; Wan-Taek Im (Archives of Microbiology, 2016)

Dibenzothiophene desulfurization capability and evolutionary divergence of newly isolated bacteria - Nasrin Akhtar; Muhammad A. Ghauri; Kalsoom Akhtar (Archives of Microbiology, 2016)

Effect of Shale Distribution on Hydrocarbon Sands Integrated with Anisotropic Rock Physics for AVA Modelling: A Case Study - Aamir Ali; Zubair; Matloob Hussain; Khaista Rehman; Muhammad Toqeer (Acta Geophysica, 2016)

Dietary Isoflavones as Modulators of Drug Metabolizing Enzymes and Transporters: Effect on Prescription Medicines - Isha Taneja; Kanumuri Siva Rama Raju; Muhammad Wahajuddin (Critical Reviews in Food Science and Nutrition, 2016)

Sulphur dioxide loadings over megacity Lahore (Pakistan) and adjoining region of Indo-Gangetic Basin - Zia ul-Haq; Salman Tariq; Muhammad Ali; Khalid Mahmood; Asim Daud Rana (International Journal of Remote Sensing, 2016)

Estimation the Physical Variables of Rainwater Harvesting System Using Integrated GIS-Based Remote Sensing Approach - Khamis Naba Sayl; Nur Shazwani Muhammad; Zaher Mundher Yaseen; Ahmed El-shafie (Water Resources Management, 2016)

Pore-Network Simulation of Unstable Miscible Displacements in Porous Media - Mahnaz Hekmatzadeh; Mitra Dadvar; Muhammad Sahimi (Transport in Porous Media, 2016)

Abnormal response to methylphenidate across multiple fMRI procedures in cocaine use disorder: feasibility study - Scott J. Moeller; Anna B. Konova; Dardo Tomasi; Muhammad A. Parvaz; Rita Z. Goldstein (Psychopharmacology, 2016)

Quasi MT Inversion of Short-Offset Transient Electromagnetic Data - Wei-ying Chen; Guo-qiang Xue; Muhammad Younis Khan (Pure and Applied Geophysics, 2016)

What do we really know about alien plant invasion? A review of the invasion mechanism of one of the world’s worst weeds - Ali Ahsan Bajwa; Bhagirath Singh Chauhan; Muhammad Farooq; Asad Shabbir; Steve William Adkins (Planta, 2016)

RETRACTED ARTICLE: Floristic and ethnoecological diversity in various habitats of a semi-arid area in the Chakwal district (Pakistan), with special emphasis on medicinal plants - Mehwish Jamil Noor; Mushtaq Ahmad; Muhammad Zafar; Maliha Sarfraz; Ismail Yusoff; Yatimah Alias; Muhammad Aqeel Ashraf (Plant Ecology, 2016)

Effectiveness and benefit cost ratio of selected insecticides at different applicationon intervals for brinjal shoot and fruit borer, Leucinodes orbonalis (G.) management on brinjal, Solanum melongena (L.) at Sahiwal, Pakistan - Qudsia Yousafi; Muhammad Afzal; Muhammad Aslam; Allah Ditta Abid (Phytoparasitica, 2016)

Genome scan linkage analysis identifies quantitative trait loci affecting serum clinical–chemical traits in Korean native chicken - Dong-Won Seo; Hee-Bok Park; Shil Jin; Muhammad Cahyadi; Nuri Choi; Kang-Nyeong Heo; Cheorun Jo; Jun-Heon Lee (Molecular Biology Reports, 2016)

Piroxicam sulfonates biology-oriented drug synthesis (BIODS), characterization and anti-nociceptive screening - Safi Ullah; Muhammad Saeed; Syed Muhammad Ashhad Halimi; Muhammad Imran Fakhri; Khalid Mohammed Khan; Ikhtiar Khan; Shahnaz Perveen (Medicinal Chemistry Research, 2016)

Precipitation variability assessment of northeast China: Songhua River basin - Muhammad Imran Khan; Dong Liu; Qiang Fu; Muhammad Azmat; Mingjie Luo; Yuxiang Hu; Yongjia Zhang; Faiz M Abrar (Journal of Earth System Science, 2016)

A comparative study of metal contamination in soil using the borehole method - T. L. Teh; Nik Norulaini Nik Ab Rahman; Mohammad Shahadat; Y. S. Wong; Muhammad I. Syakir; A. K. Mohd Omar (Environmental Monitoring and Assessment, 2016)

Anticoccidial effect of mananoligosacharide against experimentally induced coccidiosis in broiler - Naila Chand; Hassan Faheem; Rifat Ullah Khan; Muhammad Subhan Qureshi; Ibrahim A. Alhidary; Alaeldein M. Abudabos (Environmental Science and Pollution Research, 2016)

Degradation of chlorinated organic solvents in aqueous percarbonate system using zeolite supported nano zero valent iron (Z-nZVI) composite - Muhammad Danish; Xiaogang Gu; Shuguang Lu; Muhammad Naqvi (Environmental Science and Pollution Research, 2016)

Bioaccumulation of Heavy Metals in Different Organs of Wallago attu from River Kabul Khyber Pakhtunkhwa, Pakistan - Muhammad Siraj; Muhammad Khisroon; Ajmal Khan (Biological Trace Element Research, 2016)

Toxicity of Nano-Titanium Dioxide (TiO2-NP) Through Various Routes of Exposure: a Review - Muhammad Shakeel; Farhat Jabeen; Samina Shabbir; Muhammad Saleem Asghar; Muhammad Saleem Khan; Abdul Shakoor Chaudhry (Biological Trace Element Research, 2016)

Probiotic delivery systems: a brief overview - Jihyun Kim; Naeem Muhammad; Byung Hak Jhun; Jin-Wook Yoo (Journal of Pharmaceutical Investigation, 2016)

Spatial assessment of forest cover and land-use changes in the Hindu-Kush mountain ranges of northern Pakistan - Sami Ullah; Muhammad Farooq; Muhammad Shafique; Muhammad Afra Siyab; Fazli Kareem; Matthias Dees (Journal of Mountain Science, 2016)

Pcal_0768, a hyperactive 4-α-glucanotransferase from Pyrobacculum calidifontis - Sumaira Mehboob; Nasir Ahmad; Naeem Rashid; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2016)

Molecular characterization and growth optimization of halo-tolerant protease producing Bacillus Subtilis Strain BLK-1.5 isolated from salt mines of Karak, Pakistan - Nawab Ali; Nimat Ullah; Muhammad Qasim; Hazir Rahman; Shahid Niaz Khan; Abdul Sadiq; Muhammad Adnan (Extremophiles, 2016)

Molecular characterization of infectious bursal disease viruses from Pakistan - Muhammad Zubair Shabbir; Muhammad Ali; Muhammad Abbas; Umer Naveed Chaudhry; Zia-ur-Rehman; Muhammad Munir (Archives of Virology, 2016)

Optimization of chlorination boosters in drinking water distribution network for Al-Khobar City in Saudi Arabia - Muhammad Nadeem Sharif; Ashraf Farahat; Muhammad A. Al-Zahrani; Nilufar Islam; Manuel J. Rodriguez; Rehan Sadiq (Arabian Journal of Geosciences, 2016)

AM1 is a potential ABA substitute for drought tolerance as revealed by physiological and ultra-structural responses of oilseed rape - Muhammad Shahbaz Naeem; Lulu Dai; Farooq Ahmad; Ashfaq Ahmad; Jun Li; Chunlei Zhang (Acta Physiologiae Plantarum, 2016)

Phenolic, flavonoid contents, anticholinesterase and antioxidant evaluation of Iris germanica var ; florentina - Farhat Ullah; Muhammad Ayaz; Abdul Sadiq; Abid Hussain; Sajjad Ahmad; Muhammad Imran; Anwar Zeb (Natural Product Research, 2016)

Parameter Identification of Nonlinear Muskingum Model with Backtracking Search Algorithm - Xiaohui Yuan; Xiaotao Wu; Hao Tian; Yanbin Yuan; Rana Muhammad Adnan (Water Resources Management, 2016)

Rotavirus infections in Detroit, USA, a region of low vaccine prevalence - Nahed Abdel-Haq; Muhammad Amjad; Eric McGrath; Hossein Salimnia; Marilynn Fairfax; Basim I. Asmar (VirusDisease, 2016)

Association of tomato leaf curl Sudan virus with leaf curl disease of tomato in Jeddah, Saudi Arabia - Sayed Sartaj Sohrab; Muhammad Yasir; Sherif Ali El-Kafrawy; Ayman T. Abbas; Magdi Ali Ahmed Mousa; Ahmed A. Bakhashwain (VirusDisease, 2016)

The use of FAMACHA in estimation of gastrointestinal nematodes and total worm burden in Damara and Barbados Blackbelly cross sheep - Konto Mohammed; Yusuf Abba; Nur Syairah Binti Ramli; Murugaiyah Marimuthu; Mohammed Ariff Omar; Faez Firdaus Jesse Abdullah; Muhammad Abubakar Sadiq; Abdulnasir Tijjani; Eric Lim Teik Chung; Mohammed Azmi Mohammed Lila (Tropical Animal Health and Production, 2016)

Molecular Analysis of Drought Tolerance in Guava Based on In Vitro PEG Evaluation - Eman Abouzaid; El-Sayed N. El-Sayed; El-Sayed A. Mohamed; Muhammad Youssef (Tropical Plant Biology, 2016)

Angiogenic potential of extracellular matrix of human amniotic membrane - Siti Nurnasihah Md Hashim; Muhammad Fuad Hilmi Yusof; Wafa’ Zahari; Khairul Bariah Ahmad Amin Noordin; Thirumulu Ponnuraj Kannan; Suzina Sheikh Abdul Hamid; Khairani Idah Mokhtar; Azlina Ahmad (Tissue Engineering and Regenerative Medicine, 2016)

Prediction of Protein Submitochondrial Locations by Incorporating Dipeptide Composition into Chou’s General Pseudo Amino Acid Composition - Khurshid Ahmad; Muhammad Waris; Maqsood Hayat (The Journal of Membrane Biology, 2016)

A study on the enhancing earthquake frequency in northern Pakistan: is the climate change responsible? - Muhammad Usman (Natural Hazards, 2016)

Differential Effects of Plant Growth-Promoting Rhizobacteria on Maize Growth and Cadmium Uptake - Iftikhar Ahmad; Muhammad Javed Akhtar; Hafiz Naeem Asghar; Umber Ghafoor; Muhammad Shahid (Journal of Plant Growth Regulation, 2016)

A New Broad-Spectrum Peptide Antibiotic Produced by Bacillus brevis Strain MH9 Isolated from Margalla Hills of Islamabad, Pakistan - Syed Aun Muhammad; Amjad Ali; Anam Naz; Afreenish Hassan; Naeem Riaz; Syed Saeed-ul-Hassan; Saadia Andleeb; Debmalya Barh (International Journal of Peptide Research and Therapeutics, 2016)

Differential accumulation of potassium results in varied salt-tolerance response in tomato (Solanum lycopersicum L.) cultivars - Muhammad Amjad; Javaid Akhtar; Behzad Murtaza; Ghulam Abbas; Husnain Jawad (Horticulture, Environment, and Biotechnology, 2016)

Prevalence of Waterborne Diseases in Exposed and Unexposed Clusters Using Biosand Filters in a Rural Community, Sindh, Pakistan - Munir Ahmed Sheikh; Muhammad Ayaz Mustufa; Taj Muhammad Laghari; Binafsha Manzoor; Syed Ali Haider; Safia Bibi; Firdous Imran Ali (Exposure and Health, 2016)

Assessment of seasonal variation for air pollutant accumulation by Zizyphus tree under washing treatment - Mohamed Abdulraheem Shaheen; Fathy Saad El-Nakhlawy; Fahd Mosallam Almehmadi; Muhammad Zahid Ihsan; Abdulmohsin Rajeh Al-Shareef (Environmental Monitoring and Assessment, 2016)

Effects of industrial wastewater on growth and biomass production in commonly grown vegetables - Syeda Uzma; Azizullah Azizullah; Roqaia Bibi; Farhat Nabeela; Uzair Muhammad; Imran Ali; Zia Ur Rehman; Donat-Peter Häder (Environmental Monitoring and Assessment, 2016)

Health risk assessment from contaminated foodstuffs: a field study in chromite mining-affected areas northern Pakistan - Javed Nawab; Gang Li; Sardar Khan; Hassan Sher; Muhammad Aamir; Isha Shamshad; Anwarzeb Khan; Muhammad Amjad Khan (Environmental Science and Pollution Research, 2016)

Escherichia coli as a fatty acid and biodiesel factory: current challenges and future directions - Ziaur Rahman; Naim Rashid; Javed Nawab; Muhammad Ilyas; Bong Hyun Sung; Sun Chang Kim (Environmental Science and Pollution Research, 2016)

Osmoregulation and antioxidant production in maize under combined cadmium and arsenic stress - Shakeel Ahmad Anjum; Mohsin Tanveer; Saddam Hussain; Babar Shahzad; Umair Ashraf; Shah Fahad; Waseem Hassan; Saad Jan; Imran Khan; Muhammad Farrukh Saleem; Ali Ahsan Bajwa; Longchang Wang; et al. (Environmental Science and Pollution Research, 2016)

Bisphenol A exposure and healing effects of Adiantum capillus-veneris L. plant extract (APE) in bisphenol A-induced reproductive toxicity in albino rats - Balal Yousaf; Amina; Guijian Liu; Ruwei Wang; Abdul Qadir; Muhammad Ubaid Ali; Qudsia Kanwal; Bushra Munir; Asmatullah; Zaigham Abbas (Environmental Science and Pollution Research, 2016)

Use of RSM modeling for optimizing decolorization of simulated textile wastewater by Pseudomonas aeruginosa strain ZM130 capable of simultaneous removal of reactive dyes and hexavalent chromium - Zahid Maqbool; Sabir Hussain; Tanvir Ahmad; Habibullah Nadeem; Muhammad Imran; Azeem Khalid; Muhammad Abid; Fabrice Martin-Laurent (Environmental Science and Pollution Research, 2016)

Multi-objective optimization model for water resource management: a case study for Riyadh, Saudi Arabia - Muhammad Al-Zahrani; Ammar Musa; Shakhawat Chowdhury (Environment, Development and Sustainability, 2016)

Quantitative trait locus mapping for salt tolerance at maturity stage in indica rice using replicated F2 population - Md. Shah Kamal Khan; Muhammad Saeed; Javed Iqbal (Brazilian Journal of Botany, 2016)

Foliar treatment with Lolium perenne (Poaceae) leaf extract alleviates salinity and nickel-induced growth inhibition in pea - Rashad Mukhtar Balal; Muhammad Adnan Shahid; Muhammad Mansoor Javaid; Muhammad Akbar Anjum; Hafiz Haider Ali; Neil Scott Mattson; Francisco Garcia-Sanchez (Brazilian Journal of Botany, 2016)

Assessment of Serum Trace Elements in Diarrheic Yaks (Bos grunniens) in Hongyuan, China - Zhaoqing Han; Rongrong Li; Kun Li; Muhammad Shahzad; Xiao Qiang Wang; Wenteng Jiang; Houqiang Luo; Gang Qiu; Fazul Nabi; Jiakui Li; Xianrong Meng (Biological Trace Element Research, 2016)

Psychrophilic and psychrotrophic fungi: a comprehensive review - Noor Hassan; Muhammad Rafiq; Muhammad Hayat; Aamer Ali Shah; Fariha Hasan (Reviews in Environmental Science and Bio/Technology, 2016)

An efficient regeneration system and steviol glycoside analysis of Stevia rebaudiana Bertoni, a source of natural high-intensity sweetener - Buhara Yücesan; Refik Büyükgöçmen; Aliyu Mohammed; Muhammad Sameeullah; Cevher Altuğ; Songül Gürel; Ekrem Gürel (In Vitro Cellular & Developmental Biology - Plant, 2016)

In vitro propagation and cardenolide profiling of Digitalis ferruginea subsp. schischkinii, a medicinally important foxglove species with limited distribution in Northern Turkey - Buhara Yücesan; Aliyu Mohammed; İsmail Eker; Muhammad Sameeullah; Öznur Demir-Ordu; Cansu Cihangir; Nevin Şahbaz; Özge Kaya; Frieder Müller-Uri; Wolfgang Kreis; Ekrem Gürel (In Vitro Cellular & Developmental Biology - Plant, 2016)

Petrology and geochemistry of Jura granite and granite gneiss in the Neelum Valley, Lesser Himalayas (Kashmir, Pakistan) - Muhammad Saleem Mughal; Muhammad Sabir Khan; Muhammad Rustam Khan; Sohail Mustafa; Fahad Hameed; Muhammad Basharat; Abrar Niaz (Arabian Journal of Geosciences, 2016)

Geochemistry and petrology of Late Miocene-Pleistocene Dibdibba sandstone formation in south and central Iraq: implications for provenance and depositional setting - Salih Muhammad Awadh; Zinah Saleem Al-Ankaz (Arabian Journal of Geosciences, 2016)

The role of selenium in amelioration of heat-induced oxidative damage in cucumber under high temperature stress - Rashad Mukhatar Balal; Muhammad Adnan Shahid; Muhammad Mansoor Javaid; Zafar Iqbal; Muhammad Akbar Anjum; Francisco Garcia-Sanchez; Neil Scott Mattson (Acta Physiologiae Plantarum, 2016)

Chaetomium endophytes: a repository of pharmacologically active metabolites - Nighat Fatima; Syed Aun Muhammad; Ibrar Khan; Muneer Ahmed Qazi; Irum Shahzadi; Amara Mumtaz; Muhammad Ali Hashmi; Abida Kalsoom Khan; Tariq Ismail (Acta Physiologiae Plantarum, 2016)

What drives the willingness to pay for crop insurance against extreme weather events (flood and drought) in Pakistan? A hypothetical market approach - Muhammad Arshad; T.S. Amjath-Babu; Harald Kächele; Klaus Müller (Climate and Development, 2016)

The role of new eudesmane-type sesquiterpenoid and known eudesmane derivatives from the red alga Laurencia obtusa as potential antifungal–antitumour agents - Walied M. Alarif; Khalid O. Al-Footy; Muhammad Sulaiman Zubair; Mohamed Halid PH; Mohamed A. Ghandourah; Salim A. Basaif; Sultan S. Al-Lihaibi; Seif-Eldin N. Ayyad; Farid A. Badria (Natural Product Research, 2016)

Biofunctional properties of Eruca sativa Miller (rocket salad) hydroalcoholic extract - Khushbakht Sultan; Muhammad Zakir; Haroon Khan; Abdur Rauf; Noor Ul Akber; Murad Ali Khan (Natural Product Research, 2016)

Anti-tumour-promoting and thermal-induced protein denaturation inhibitory activities of β-sitosterol and lupeol isolated from Diospyros lotus L. - Abdur Rauf; Ghias Uddin; Haroon Khan; Muslim Raza; Muhammad Zafar; Harukuni Tokuda (Natural Product Research, 2016)

A novel antimicrobial flavonoid from the stem bark of Commiphora pedunculata (Kotschy & Peyr.) Engl. - Nasir Tajuddeen; Muhammad S. Sallau; Aliyu M. Musa; Sani M. Yahaya; James D. Habila; Abdullahi Musa Ismail (Natural Product Research, 2016)

Beta-haemolytic streptococcal endocarditis: clinical presentation, management and outcomes - Abdelghani El Rafei; Daniel C. DeSimone; Christopher V. DeSimone; Brian D. Lahr; James M. Steckelberg; Muhammad R. Sohail; Walter R. Wilson; Larry M. Baddour (Infectious Diseases, 2016)

Banana peel: an effective biosorbent for aflatoxins - Zahid Hussain Shar; Mary T. Fletcher; Gul Amer Sumbal; Syed Tufail Hussain Sherazi; Cindy Giles; Muhammad Iqbal Bhanger; Shafi Muhammad Nizamani (Food Additives & Contaminants: Part A, 2016)

OpenDA-NEMO framework for ocean data assimilation - Nils van Velzen; Muhammad Umer Altaf; Martin Verlaan (Ocean Dynamics, 2016)

Synthesis and evaluation of some novel N-substituted rhodanines for their anticancer activity - Sulaiman Ali Muhammad; Subban Ravi; Arumugam Thangamani (Medicinal Chemistry Research, 2016)

In silico transcriptional regulation and functional analysis of dengue shock syndrome associated SNPs in PLCE1 and MICB genes - Malik Mumtaz Taqi; Durdana Waseem; Humaira Ismatullah; Syed Aleem Haider; Muhammad Faisal (Functional & Integrative Genomics, 2016)

QTL mapping for salt tolerance at seedling stage in the interspecific cross of Gossypium tomentosum with Gossypium hirsutum - George Oluoch; Juyun Zheng; Xingxing Wang; Muhammad Kashif Riaz Khan; Zhongli Zhou; Xiaoyan Cai; Chunying Wang; Yuhong Wang; Xueyuan Li; Heng Wang; Fang Liu; Kunbo Wang (Euphytica, 2016)

A critical re-evaluation of controls on spatial and seasonal variations in nitrate concentrations in river waters throughout the River Derwent catchment in North Yorkshire, UK - Shaheen Begum; Muhammad Adnan; Colin J. McClean; Malcolm S. Cresser (Environmental Monitoring and Assessment, 2016)

Gaseous pollutants from brick kiln industry decreased the growth, photosynthesis, and yield of wheat (Triticum aestivum L.) - Muhammad Adrees; Muhammad Ibrahim; Aamir Mehmood Shah; Farhat Abbas; Farhan Saleem; Muhammad Rizwan; Saadia Hina; Fariha Jabeen; Shafaqat Ali (Environmental Monitoring and Assessment, 2016)

Economic assessment of different mulches in conventional and water-saving rice production systems - Khawar Jabran; Mubshar Hussain; Shah Fahad; Muhammad Farooq; Ali Ahsan Bajwa; Hesham Alharrby; Wajid Nasim (Environmental Science and Pollution Research, 2016)

Alleviation of lead-induced physiological, metabolic, and ultramorphological changes in leaves of upland cotton through glutathione - Mumtaz Khan; M. K. Daud; Ali Basharat; Muhammad Jamil Khan; Azizullah Azizullah; Niaz Muhammad; Noor Muhammad; Zia ur Rehman; Shui Jin Zhu (Environmental Science and Pollution Research, 2016)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Erratum to: Production of an oligosaccharide-specific cellobiohydrolase from the thermophilic fungus Thielavia terrestris - James Sy-Keen Woon; Mukram Mohamed Mackeen; Amirul Husna bin Sudin; Nor Muhammad Mahadi; Rosli Md Illias; Abdul Munir Abdul Murad; Farah Diba Abu Bakar (Biotechnology Letters, 2016)

Production of an oligosaccharide-specific cellobiohydrolase from the thermophilic fungus Thielavia terrestris - James Sy-Keen Woon; Mukram Mohamed Mackeen; Amirul Husna bin Sudin; Nor Muhammad Mahadi; Rosli Md Illias; Abdul Munir Abdul Murad; Farah Diba Abu Bakar (Biotechnology Letters, 2016)

Spatial distribution and catalytic mechanisms of β-glucosidase activity at the root-soil interface - Muhammad Sanaullah; Bahar S. Razavi; Evgenia Blagodatskaya; Yakov Kuzyakov (Biology and Fertility of Soils, 2016)

Relationship between in vitro characterization and comparative efficacy of plant growth-promoting rhizobacteria for improving cucumber salt tolerance - Sajid Mahmood Nadeem; Maqshoof Ahmad; Muhammad Naveed; Muhammad Imran; Zahir Ahmad Zahir; David E. Crowley (Archives of Microbiology, 2016)

Sediment yield assessment and identification of check dam sites for Rawal Dam catchment - Nida Samad; Muhammad Hamid Chauhdry; Muhammad Ashraf; Muhammad Saleem; Qudsia Hamid; Umair Babar; Hassan Tariq; Muhammad Shahid Farid (Arabian Journal of Geosciences, 2016)

Flood modeling and simulations using hydrodynamic model and ASTER DEM—A case study of Kalpani River - Sana Ullah; Muhammad Farooq; Tahir Sarwar; Mohammad Javed Tareen; Mirza Abdul Wahid (Arabian Journal of Geosciences, 2016)

Identifying the sources and geochemical evolution of groundwater using stable isotopes and hydrogeochemistry in the Quaternary aquifer in the area between Ismailia and El Kassara canals, Northeastern Egypt - Muhammad Gomaah; Thomas Meixner; E. A. Korany; Hassan Garamoon; Mohamed A. Gomaa (Arabian Journal of Geosciences, 2016)

Fault-controlled, bedding-parallel dolomite in the middle Jurassic Samana Suk Formation in Margalla Hill Ranges, Khanpur area (North Pakistan): petrography, geochemistry, and petrophysical characteristics - Mumtaz Muhammad Shah; Waqar Ahmed; Naveed Ahsan; Mona Lisa (Arabian Journal of Geosciences, 2016)

Fracture reopening by micro-earthquakes, a mechanism for oil seepage in mildly active rifts: a case study from Gemsa oilfield, the southern Gulf of Suez rift, Egypt - Shawky Sakran; Muhammad Nabih; Ahmed Henaish; Abdelmohsen Ziko (Arabian Journal of Geosciences, 2016)

Detrital mode and whole-rock geochemistry of the Miocene-Pliocene fluvial succession, Pishin Belt, Pakistan: implications on provenance and source area weathering in peripheral foreland basins - Aimal Khan Kasi; Akhtar Muhammad Kassi; Henrik Friis; Muhammad Umar; Mohibullah Mohibullah; Muhammad Ishaq Kakar (Arabian Journal of Geosciences, 2016)

Stability assessment of the curve number methodology used to estimate excess rainfall in forest-dominated watersheds - Muhammad Ajmal; Tae-Woong Kim; Jae-Hyun Ahn (Arabian Journal of Geosciences, 2016)

Phytochemistry of Daphne oleoides - Muhammad Riaz; Asma Saleem; Shabana Siddique; Bilal Ahmad Khan; Mohammad Nur-e-Alam; Syed Shahzad-ul-Hussan; Ghulam Abbas Miana; Muhammad Qayyum Khan (Natural Product Research, 2016)

Purification and biochemical properties of SDS-stable low molecular weight alkaline serine protease from Citrullus colocynthis - Muhammad Bashir Khan; Hidayatullah Khan; Muhammad Usman Shah; Sanaullah Khan (Natural Product Research, 2016)

A review of steroids from Sarcophyton species - Muhammad Sulaiman Zubair; Khalid O. Al-Footy; Seif-Eldin N. Ayyad; Sultan S. Al-Lihaibi; Walied M. Alarif (Natural Product Research, 2016)

New dammarane and ursane-type triterpenoids from the flower of Ixora coccinea Linn. - Ambreen Ikram; Muhammad Ali Versiani; Amna Khatoon; Salman Khalid Ahmed; Samina Abdul Sattar; Shaheen Faizi (Natural Product Research, 2016)

Aflatoxins in composite spices collected from local markets of Karachi, Pakistan - Muhammad Asif Asghar; Erum Zahir; Summan Rantilal; Aftab Ahmed; Javed Iqbal (Food Additives & Contaminants Part B-Surveillance, 2016)

Fatty acid compositional changes during the embryonic development of the swimming crab, Portunus pelagicus (Portunidae: Decapoda) - Nicholas Romano; Muhammad Asyraf Safee; Mahdi Ebrahimi; Aziz Arshad (Invertebrate Reproduction & Development, 2016)

Resistance risk analysis to acetamiprid and other insecticides in Acetamiprid-Selected population of Phenacoccus solenopsis - Mamuna Ijaz; Muhammad Babar Shahzad Afzal; Sarfraz Ali Shad (Phytoparasitica, 2016)

Using PCA in evaluating event-controlling attributes of landsliding in the 2005 Kashmir earthquake region, NW Himalayas, Pakistan - Muhammad Basharat; Abid Ali; Ishtiaq A. K. Jadoon; Joachim Rohn (Natural Hazards, 2016)

Characterization of Prototheca zopfii Genotypes Isolated from Cases of Bovine Mastitis and Cow Barns in China - Muhammad Shahid; Tariq Ali; Limei Zhang; Rongguang Hou; Shiyao Zhang; Laidi Ding; Dandan Han; Zhaoju Deng; Abdur Rahman; Bo Han (Mycopathologia, 2016)

Exposure to mobile phone electromagnetic field radiation, ringtone and vibration affects anxiety-like behaviour and oxidative stress biomarkers in albino wistar rats - Abubakar Shehu; Aliyu Mohammed; Rabiu Abdussalam Magaji; Mustapha Shehu Muhammad (Metabolic Brain Disease, 2016)

Management of human health risk in the context of kitchen gardens polluted by lead and cadmium near a lead recycling company - Stéphane Mombo; Yann Foucault; Frédéric Deola; Irène Gaillard; Sylvaine Goix; Muhammad Shahid; Eva Schreck; Antoine Pierart; Camille Dumat (Journal of Soils and Sediments, 2016)

Relationship between rhizosphere acidification and phytoremediation in two acacia species - Ghulam Abbas; Muhammad Saqib; Javaid Akhtar; Ghulam Murtaza; Muhammad Shahid; Amjad Hussain (Journal of Soils and Sediments, 2016)

Identification of a highly immunogenic mouse breast cancer sub cell line, 4T1-S - Hirotake Abe; Haruka Wada; Muhammad Baghdadi; Sayaka Nakanishi; Yuu Usui; Takahiro Tsuchikawa; Toshiaki Shichinohe; Satoshi Hirano; Ken-ichiro Seino (Human Cell, 2016)

Tissue specific metal characterization of selected fish species in Pakistan - Mukhtiar Ahmed; Taufiq Ahmad; Muhammad Liaquat; Kashif Sarfraz Abbasi; Ibrahim Bayoumi Abdel Farid; Muhammad Jahangir (Environmental Monitoring and Assessment, 2016)

Plant-driven removal of heavy metals from soil: uptake, translocation, tolerance mechanism, challenges, and future perspectives - Sveta Thakur; Lakhveer Singh; Zularisam Ab Wahid; Muhammad Faisal Siddiqui; Samson Mekbib Atnaw; Mohd Fadhil Md Din (Environmental Monitoring and Assessment, 2016)

Mobilization and transport of metal-rich colloidal particles from mine tailings into soil under transient chemical and physical conditions - Cong Lu; Yaoguo Wu; Sihai Hu; Muhammad Ali Raza; Yilin Fu (Environmental Science and Pollution Research, 2016)

Revisiting the emissions-energy-trade nexus: evidence from the newly industrializing countries - Khalid Ahmed; Muhammad Shahbaz; Phouphet Kyophilavong (Environmental Science and Pollution Research, 2016)

Enhanced degradation of benzene by percarbonate activated with Fe(II)-glutamate complex - Xiaori Fu; Xiaogang Gu; Shuguang Lu; Zhouwei Miao; Minhui Xu; Xiang Zhang; Muhammad Danish; Hang Cui; Usman Farooq; Zhaofu Qiu; Qian Sui (Environmental Science and Pollution Research, 2016)

Effects of dicyandiamide and dolomite application on N2O emission from an acidic soil - Muhammad Shaaban; Yupeng Wu; Qi-an Peng; Shan Lin; Yongliang Mo; Lei Wu; Ronggui Hu; Wei Zhou (Environmental Science and Pollution Research, 2016)

The impact of CO2 emissions on economic growth: evidence from selected higher CO2 emissions economies - Muhammad Azam; Abdul Qayyum Khan; Hussin Bin Abdullah; Muhammad Ejaz Qureshi (Environmental Science and Pollution Research, 2016)

Growth stage-based modulation in physiological and biochemical attributes of two genetically diverse wheat (Triticum aestivum L.) cultivars grown in salinized hydroponic culture - Muhammad Arslan Ashraf; Muhammad Ashraf (Environmental Science and Pollution Research, 2016)

Toxicity Appraisal of Untreated Dyeing Industry Wastewater Based on Chemical Characterization and Short Term Bioassays - Muhammad Furqan Akhtar; Muhammad Ashraf; Aqeel Javeed; Aftab Ahmad Anjum; Ali Sharif; Ammara Saleem; Bushra Akhtar; Abdul Muqeet Khan; Imran Altaf (Bulletin of Environmental Contamination and Toxicology, 2016)

Synergism of polyamines and plant growth regulators enhanced morphogenesis, stevioside content, and production of commercially important natural antioxidants in Stevia rebaudiana Bert - Shahid Akbar Khalil; Nasir Kamal; Muhammad Sajid; Nisar Ahmad; Roshan Zamir; Naveed Ahmad; Shahid Ali (In Vitro Cellular & Developmental Biology - Plant, 2016)

Application of infrared thermography for temperature distributions in fluid-saturated porous media - Muhammad Imran; Hamidreza M. Nick; Ruud J. Schotting (Arabian Journal of Geosciences, 2016)

Landslide susceptibility mapping using GIS and weighted overlay method: a case study from NW Himalayas, Pakistan - Muhammad Basharat; Hamid Raza Shah; Nasir Hameed (Arabian Journal of Geosciences, 2016)

Benthic foraminifera in sandy (siliciclastic) coastal sediments of the Arabian Gulf (Saudi Arabia): a technical report - Muhammad Arslan; Michael A. Kaminski; Bassam S. Tawabini; Muhammad Ilyas; Fabrizio Frontalini (Arabian Journal of Geosciences, 2016)

Evaluation of source rocks using one dimensional maturity modeling in Lower Indus Basin, Pakistan - Faisal Qayyum; Muhammad Hanif; Muhammad Mujtaba; Sohail Wahid; Fahad Ali (Arabian Journal of Geosciences, 2016)

Rice (Oryza sativa L.) hydraulic conductivity links to leaf venation architecture under well-watered condition rather than PEG-induced water deficit - Muhammad Adnan Tabassum; Yuhui Ye; Tingting Yu; Guanglong Zhu; Muhammad Shahid Rizwan; Muhammad Atif Wahid; Shaobing Peng; Yong Li (Acta Physiologiae Plantarum, 2016)

Morpho-anatomical and physiological adaptations to high altitude in some Aveneae grasses from Neelum Valley, Western Himalayan Kashmir - Khawaja Shafique Ahmad; Mansoor Hameed; Sana Fatima; Muhammad Ashraf; Farooq Ahmad; Mehwish Naseer; Noreen Akhtar (Acta Physiologiae Plantarum, 2016)

Foliar NK application mitigates drought effects in sunflower (Helianthus annuus L.) - Rai Altaf Hussain; Rashid Ahmad; Fahim Nawaz; Muhammad Yasin Ashraf; Ejaz Ahmad Waraich (Acta Physiologiae Plantarum, 2016)

Promotion of wound healing by Plantago major L. leaf extracts – ex-vivo experiments confirm experiences from traditional medicine - Muhammad Zubair; Hilde Nybom; Christina Lindholm; Johanna M. Brandner; Kimmo Rumpunen (Natural Product Research, 2016)

Remediation of arsenic-contaminated water using agricultural wastes as biosorbents - Muhammad Bilal Shakoor; Nabeel Khan Niazi; Irshad Bibi; Ghulam Murtaza; Anitha Kunhikrishnan; Balaji Seshadri; Muhammad Shahid; Shafaqat Ali; Nanthi S. Bolan; Yong Sik Ok; Muhammad Abid; Fawad Ali (Critical Reviews in Environmental Science and Technology, 2016)

Excess Stormwater Quantification in Ungauged Watersheds Using an Event-Based Modified NRCS Model - Muhammad Ajmal; Jae-Hyun Ahn; Tae-Woong Kim (Water Resources Management, 2016)

Complete genome sequencing and comparative analysis of three dengue virus type 2 Pakistani isolates - Madiha Akram; Muhammad Idrees (VirusDisease, 2016)

Risk factors associated with Mycobacterium bovis skin positivity in cattle and buffalo in Peshawar, Pakistan - Irfan Khattak; Muhammad Hassan Mushtaq; Mansur ud Din Ahmad; Muhammad Sarwar Khan; Mamoona chaudhry; Umer Sadique (Tropical Animal Health and Production, 2016)

Benzamide sulfonamide derivatives: potent inhibitors of carbonic anhydrase-II - Muhammad Saleem; Aamer Saeed; Atia-tul-Wahab; Ajmal Khan; Sanaullah Abbasi; Waqasuddin Khan; Sher Bahadar Khan; M. Iqbal Choudhary (Medicinal Chemistry Research, 2016)

Ginsenoside Rg5:Rk1 attenuates TNF-α/IFN-γ-induced production of thymus- and activation-regulated chemokine (TARC/CCL17) and LPS-induced NO production via downregulation of NF-κB/p38 MAPK/STAT1 signaling in human keratinocytes and macrophages - Sungeun Ahn; Muhammad Hanif Siddiqi; Veronica Castro Aceituno; Shakina Yesmin Simu; Jinglou Zhang; Zuly Elizabeth Jimenez Perez; Yu-Jin Kim; Deok-Chun Yang (In Vitro Cellular & Developmental Biology - Animal, 2016)

Accumulation of Residual Antibiotics in the Vegetables Irrigated by Pharmaceutical Wastewater - Shoaib Hussain; Muhammad Naeem; Muhammad Nawaz Chaudhry; Muhammad Adnan Iqbal (Exposure and Health, 2016)

Genetic variation for flowering time and height reducing genes and important traits in western Canadian spring wheat - Hua Chen; Neshat Pazooki Moakhar; Muhammad Iqbal; Curtis Pozniak; Pierre Hucl; Dean Spaner (Euphytica, 2016)

Poverty within watershed and environmentally protected areas: the case of the indigenous community in Peninsular Malaysia - Fatimah Binti Kari; Muhammad Mehedi Masud; Siti Rohani Binti Yahaya; Md. Khaled Saifullah (Environmental Monitoring and Assessment, 2016)

Perspectives and applications of nanotechnology in water treatment - Sunandan Baruah; Muhammad Najam Khan; Joydeep Dutta (Environmental Chemistry Letters, 2016)

Subcellular distribution, modulation of antioxidant and stress-related genes response to arsenic in Brassica napus L. - Muhammad A. Farooq; Rafaqat A. Gill; Basharat Ali; Jian Wang; Faisal Islam; Shafaqat Ali; Weijun Zhou (Ecotoxicology, 2016)

Experimental analysis of the effects of consumer exclusion on recruitment and succession of a coral reef system along a water quality gradient in the Spermonde Archipelago, Indonesia - Jeremiah G. Plass-Johnson; Jasmin P. Heiden; Nur Abu; Muhammad Lukman; Mirta Teichberg (Coral Reefs, 2016)

Karakorum temperature out of phase with hemispheric trends for the past five centuries - Muhammad Usama Zafar; Moinuddin Ahmed; Mukund Palat Rao; Brendan M. Buckley; Nasrullah Khan; Muhammad Wahab; Jonathan Palmer (Climate Dynamics, 2016)

A Novel Approach Based on Data Redundancy for Feature Extraction of EEG Signals - Hafeez Ullah Amin; Aamir Saeed Malik; Nidal Kamel; Muhammad Hussain (Brain Topography, 2016)

Thiourea-induced metabolic changes in two mung bean [Vigna radiata (L.) Wilczek] (Fabaceae) varieties under salt stress - Shagufta Perveen; Rabia Farooq; Muhammad Shahbaz (Brazilian Journal of Botany, 2016)

Towards better insect management strategy: restriction of insecticidal gene expression to biting sites in transgenic cotton - Emine Anayol; Allah Bakhsh; Ömer Cem Karakoç; Selma Onarıcı; Deniz Köm; Muhammad Aasim; Sancar Fatih Özcan; Surendra Barpete; Saber D. Khabbazi; Burak Önol; Cengiz Sancak; Khalid M. Khawar; et al. (Plant Biotechnology Reports, 2016)

Towards Co-PPGIS—a collaborative public participatory GIS-based measure for transparency in housing schemes: a case of Lahore, Pakistan - Muhammad A. Butt; Songnian Li; Nasir Javed (Applied Geomatics, 2016)

Climate‐driven changes to the spatio‐temporal distribution of the parasitic nematode, Haemonchus contortus, in sheep in Europe - Hannah Rose; Cyril Caminade; Muhammad Bashir Bolajoko; Paul Phelan; Jan van Dijk; Matthew Baylis; Diana Williams; Eric R. Morgan (Global Change Biology, 2016)
Recent climate change has resulted in changes to the phenology and distribution of invertebrates worldwide. Where invertebrates are associated with disease, climate variability and changes in climate may also affect the spatio‐temporal dynamics of disease. Due to its significant impact on sheep production and welfare, the recent increase in diagnoses of ovine haemonchosis caused by the nematode Haemonchus contortus in some temperate regions is particularly concerning. This study is the first to evaluate the impact of climate change on H. contortus at a continental scale. A model of the basic reproductive quotient of macroparasites, Q 0 , adapted to H. contortus and extended to incorporate environmental stochasticity and parasite behaviour, was used to simulate Pan‐European spatio‐temporal changes in H. contortus infection pressure under scenarios of climate change. Baseline Q 0 simulations, using historic climate observations, reflected the current distribution of H. contortus in Europe. In northern Europe, the distribution of H. contortus is currently limited by temperatures falling below the development threshold during the winter months and within‐host arrested development is necessary for population persistence over winter. In southern Europe, H. contortus infection pressure is limited during the summer months by increased temperature and decreased moisture. Compared with this baseline, Q 0 simulations driven by a climate model ensemble predicted an increase in H. contortus infection pressure by the 2080s. In northern Europe, a temporal range expansion was predicted as the mean period of transmission increased by 2–3 months. A bimodal seasonal pattern of infection pressure, similar to that currently observed in southern Europe, emerges in northern Europe due to increasing summer temperatures and decreasing moisture. The predicted patterns of change could alter the epidemiology of H. contortus in Europe, affect the future sustainability of contemporary control strategies, and potentially drive local adaptation to climate change in parasite populations.

Cofilin as a Promising Therapeutic Target for Ischemic and Hemorrhagic Stroke - Qasim Alhadidi; Muhammad Shahdaat Bin Sayeed; Zahoor A. Shah (Translational Stroke Research, 2016)

Differential Role of Indolebutyric Acid in Sugarcane Root Development - Ghulam Mustafa; Muhammad Sarwar Khan (Sugar Tech, 2016)

Identification and Functional Analysis of the NADK Gene Family in Wheat - Xiang Wang; Wen-Yan Li; Mao-Mao Zhang; Yin-Tao Gao; Wen-Ting Liu; Wen-Qiang Li; Izhar Muhammad; Kun-Ming Chen (Plant Molecular Biology Reporter, 2016)

Mapping QTL associated with remobilization of zinc from vegetative tissues into grains of barley (Hordeum vulgare) - Shahid Hussain; Zed Rengel; Seyed A. Mohammadi; Asghar Ebadi-Segherloo; Muhammad A. Maqsood (Plant and Soil, 2016)

Deltamethrin resistance in the cotton mealybug, Phenacoccus solenopsis Tinsley: Cross-resistance to other insecticides, fitness cost analysis and realized heritability - Bushra Saddiq; Naeem Abbas; Sarfraz Ali Shad; Muhammad Aslam; Muhammad Babar Shahzad Afzal (Phytoparasitica, 2016)

Therapeutic Efficacy of Neurostimulation for Depression: Techniques, Current Modalities, and Future Challenges - Hafsah Akhtar; Faiza Bukhari; Misbah Nazir; Muhammad Nabeel Anwar; Adeeb Shahzad (Neuroscience Bulletin, 2016)

iRSpot-GAEnsC: identifing recombination spots via ensemble classifier and extending the concept of Chou’s PseAAC to formulate DNA samples - Muhammad Kabir; Maqsood Hayat (Molecular Genetics and Genomics, 2016)

Synthesis of 2-(2-methoxyphenyl)-5-phenyl-1,3,4-oxadiazole derivatives and evaluation of their antiglycation potential - Muhammad Taha; Nor Hadiani Ismail; Waqas Jamil; Syahrul Imran; Fazal Rahim; Syed Muhammad Kashif; Mohd Zulkefeli (Medicinal Chemistry Research, 2016)

Phytoavailability of lead altered by two Pelargonium cultivars grown on contrasting lead-spiked soils - Muhammad Arshad; Georges Merlina; Gaëlle Uzu; Sophie Sobanska; Géraldine Sarret; Camille Dumat; Jérome Silvestre; Eric Pinelli; Jean Kallerhoff (Journal of Soils and Sediments, 2016)

Reproductive capacity of Heterodera schachtii on Thlaspi arvense, Capsella bursa-pastoris and varying populations of Chenopodium album - Muhammad Ahmad; Somayyeh Sedaghatjoo; Andreas Westphal (Journal of Plant Diseases and Protection, 2016)

A novel homozygous splicing mutation of CASC5 causes primary microcephaly in a large Pakistani family - Sandra Szczepanski; Muhammad Sajid Hussain; Ilknur Sur; Janine Altmüller; Holger Thiele; Uzma Abdullah; Syeda Seema Waseem; Abubakar Moawia; Gudrun Nürnberg; Angelika Anna Noegel; Shahid Mahmood Baig; Peter Nürnberg (Human Genetics, 2016)

Separation of toxic rhodamine B from aqueous solution using an efficient low-cost material, Azolla pinnata, by adsorption method - Muhammad Raziq Rahimi Kooh; Linda B. L. Lim; Lee Hoon Lim; Muhammad Khairud Dahri (Environmental Monitoring and Assessment, 2016)

Contrasting effects of untreated textile wastewater onto the soil available nitrogen-phosphorus and enzymatic activities in aridisol - Muhammad Saleem Arif; Muhammad Riaz; Sher Muhammad Shahzad; Tahira Yasmeen; Alexandre Buttler; Juan Carlos Garcıa-Gil; Mahnaz Roohi; Akhtar Rasool (Environmental Monitoring and Assessment, 2016)

Mechanisms of biochar-mediated alleviation of toxicity of trace elements in plants: a critical review - Muhammad Rizwan; Shafaqat Ali; Muhammad Farooq Qayyum; Muhammad Ibrahim; Muhammad Zia-ur-Rehman; Tahir Abbas; Yong Sik Ok (Environmental Science and Pollution Research, 2016)

PCBs attenuation and abundance of Dehalococcoides spp., bphC, CheA, and flic genes in typical polychlorinated biphenyl-polluted soil under floody and dry soil conditions - Muhammad Zaffar Hashmi; Zhihui Qin; Xiaoyan Yao; Zulkifl Ahmed; Su Xiaomei; Chaofeng Shen; Xianjin Tang (Environmental Science and Pollution Research, 2016)

Correlation studies on nitrogen for sunflower crop across the agroclimatic variability - Wajid Nasim; Hatem Belhouchette; Muhammad Tariq; Shah Fahad; Hafiz Mohkum Hammad; Muhammad Mubeen; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary; Imran Khan; Faisal Mahmood; Tauqeer Abbas; Fahd Rasul; et al. (Environmental Science and Pollution Research, 2016)

Environment and air pollution like gun and bullet for low-income countries: war for better health and wealth - Xiang Zou; Muhammad Azam; Talat Islam; Khalid Zaman (Environmental Science and Pollution Research, 2016)

Pharmaceutical wastewater being composite mixture of environmental pollutants may be associated with mutagenicity and genotoxicity - Ali Sharif; Muhammad Ashraf; Aftab Ahmed Anjum; Aqeel Javeed; Imran Altaf; Muhammad Furqan Akhtar; Mateen Abbas; Bushra Akhtar; Ammara Saleem (Environmental Science and Pollution Research, 2016)

Salt stress-induced modulations in the shoot proteome of Brassica juncea genotypes - Peerzada Yasir Yousuf; Altaf Ahmad; Arshid Hussain Ganie; Muhammad Iqbal (Environmental Science and Pollution Research, 2016)

Organic amendments impact the availability of heavy metal(loid)s in mine-impacted soil and their phytoremediation by Penisitum americanum and Sorghum bicolor - Javed Nawab; Sardar Khan; Muhammad Aamir; Isha Shamshad; Zahir Qamar; Islamud Din; Qing Huang (Environmental Science and Pollution Research, 2016)

Restoration and conservation potential of destroyed Qinghai spruce (Picea crassifolia) forests in the Qilian Mountains of northwest China - Shouzhang Peng; Chuanyan Zhao; Zhonglin Xu; Muhammad Waseem Ashiq (Mitigation and Adaptation Strategies for Global Change, 2016)

Seismic and well log driven structural and petrophysical analysis of the Lower Goru Formation in the Lower Indus Basin, Pakistan - Muhammad Naeem; Muhammad Kamran Jafri; Sayed S. R. Moustafa; Nassir S. AL-Arifi; Shazia Asim; Farhan Khan; Nisar Ahmed (Geosciences Journal, 2016)

Satellite and ground-based remote sensing of aerosols during intense haze event of October 2013 over lahore, Pakistan - Salman Tariq; ul-Haq Zia; Muhammad Ali (Asia-Pacific Journal of Atmospheric Sciences, 2016)

River bank erosion and channel evolution in sand-bed braided reach of River Chenab: role of floods during different flow regimes - Muhammad Ashraf; Muhammad Tousif Bhatti; Abdul Sattar Shakir (Arabian Journal of Geosciences, 2016)

Species-specific detection of Vibrio alginolyticus in shellfish and shrimp by real-time PCR using the groEL gene - Raju Ahmed; S. M. Rafiquzaman; Muhammad Tofazzal Hossain; Jong-Min Lee; In-Soo Kong (Aquaculture International, 2016)

Novel Controlled Release Polymer-Lipid Formulations Processed by Hot Melt Extrusion - Mohammed Maniruzzaman; Muhammad T. Islam; Sheelagh Halsey; Devyani Amin; Dennis Douroumis (AAPS PharmSciTech, 2016)

New furocarbazole alkaloids from Lonicera quinquelocularis - Dilfaraz Khan; Shafiullah Khan; Syed Badshah; Hazrat Ali; Hamid Ullah; Zia Muhammad; Simon Woodward (Natural Product Research, 2016)

Amberinone, a new guaianolide from Amberboa ramosa - Muhammad Ibrahim; Iqbal Hussain; Nusrat Hussain; Arruje Hameed; Tahir Farooq; Amjad Hussain; Muhammad Sajid Hamid Akash; Shabbir Hussain (Natural Product Research, 2016)

A review of the pollen analysis of South Asian honey to identify the bee floras of the region - Mehwish Jamil Noor; Mushtaq Ahmad; Muhammad Aqeel Ashraf; Muhammad Zafar; Shazia Sultana (Palynology, 2016)

Wheat Allergy and Intolerence; Recent Updates and Perspectives - Imran Pasha; Farhan Saeed; Muhammad Tauseef Sultan; Rizwana Batool; Mahwash Aziz; Waqas Ahmed (Critical Reviews in Food Science and Nutrition, 2016)

Aflatoxins and ochratoxin A in export quality raisins collected from different areas of Pakistan - Muhammad Asif Asghar; Aftab Ahmed; Javed Iqbal (Food Additives & Contaminants Part B-Surveillance, 2016)

Comparative efficacy of ANN and ANFIS models in estimating biosurfactant production produced by Klebseilla sp. FKOD36 - Zulfiqar Ahmad; Muhammad Arshad; David Crowley; Benyamin Khoshnevisan; Marziye Yousefi; Muhammad Imran; Sabir Hussain (Stochastic Environmental Research and Risk Assessment, 2016)

Temporal Information of Directed Causal Connectivity in Multi-Trial ERP Data using Partial Granger Causality - Vahab Youssofzadeh; Girijesh Prasad; Muhammad Naeem; KongFatt Wong-Lin (Neuroinformatics, 2016)

Multi-temporal remote sensing data and spectral indices analysis for detection tropical rainforest degradation: case study in Kapuas Hulu and Sintang districts, West Kalimantan, Indonesia - Parwati Sofan; Yenni Vetrita; Fajar Yulianto; Muhammad Rokhis Khomarudin (Natural Hazards, 2016)

Synthesis and biological activities of 2-aminophenol-based Schiff bases and their structure–activity relationship - Muhammad Aslam; Itrat Anis; Rashad Mehmood; Lubna Iqbal; Samina Iqbal; Inamullah Khan; Muhammad Salman Chishti; Shagufta Perveen (Medicinal Chemistry Research, 2016)

Effects of applying flue gas desulfurization gypsum and humic acid on soil physicochemical properties and rapeseed yield of a saline-sodic cropland in the eastern coastal area of China - Jiangkuan Nan; Xiaomin Chen; Xiaoyang Wang; Muhammad Siddique Lashari; Yuanming Wang; Zhichuang Guo; Zhenjie Du (Journal of Soils and Sediments, 2016)

Chromo/Fluorogenic Detection of Co2+, Hg2+ and Cu2+ by the Simple Schiff Base Sensor - Muhammad Saleem; Chung Ho Khang; Moon-Hwan kim; Ki Hwan Lee (Journal of Fluorescence, 2016)

Germin-like protein 2 gene promoter from rice is responsive to fungal pathogens in transgenic potato plants - Faiza Munir; Satomi Hayashi; Jacqueline Batley; Syed Muhammad Saqlan Naqvi; Tariq Mahmood (Functional & Integrative Genomics, 2016)

Identification of QTL influencing seed oil content, fatty acid profile and days to flowering in Brassica napus L. - Nasir Javed; Jianfeng Geng; Muhammad Tahir; P. B. E. McVetty; Genyi Li; Robert W. Duncan (Euphytica, 2016)

Investigation of temporal change in glacial extent of Chitral watershed using Landsat data - Usman Ali Naeem; Muhammad Ali Shamim; Naeem Ejaz; Habib ur Rehman; Umer Mustafa; Hashim Nisar Hashmi; Abdul Razzaq Ghumman (Environmental Monitoring and Assessment, 2016)

Copper-resistant bacteria reduces oxidative stress and uptake of copper in lentil plants: potential for bacterial bioremediation - Faisal Islam; Tahira Yasmeen; Qasim Ali; Muhammad Mubin; Shafaqat Ali; Muhammad Saleem Arif; Sabir Hussain; Muhammad Riaz; Farhat Abbas (Environmental Science and Pollution Research, 2016)

Evaluation of calcium and lead interaction, in addition to their impact on thyroid functions in hyper and hypothyroid patients - Nusrat Shahab Memon; Tasneem Gul Kazi; Hassan Imran Afridi; Jameel Ahmed Baig; Sadaf Sadia Arain; Oan Muhammad Sahito; Shahnawaz Baloch; Muhammad Waris (Environmental Science and Pollution Research, 2016)

Decreased fish diversity found near marble industry effluents in River Barandu, Pakistan - Shahi Mulk; Abdul Latif Korai; Azizullah Azizullah; Muhammad Nasir Khan Khattak (Ecotoxicology, 2016)

Pcal_1699, an extremely thermostable malate dehydrogenase from hyperthermophilic archaeon Pyrobaculum calidifontis - Ghazaleh Gharib; Naeem Rashid; Qamar Bashir; Qura-tul Ann Afza Gardner; Muhammad Akhtar; Tadayuki Imanaka (Extremophiles, 2016)

Reservoir attributes of a hydrocarbon-prone sandstone complex: case of the Pab Formation (Late Cretaceous) of Southwest Pakistan - Muhammad Umar; Abdul Salam Khan; Gilbert Kelling; Henrik Friis; Akhtar Muhammad Kassi (Arabian Journal of Geosciences, 2016)

Spectral decomposition application for analyzing the structure and the reservoir potential: a case study of Penobscot, Nova Scotia offshore, Canada - Shazia Asim; Salman Ahmad; Peimin Zhu; Muhammad Tayyab Naseer; Mehwish Butt (Arabian Journal of Geosciences, 2016)

Trehalose pretreatment induces drought tolerance in radish (Raphanus sativus L.) plants: some key physio-biochemical traits - Nudrat Aisha Akram; Muhammad Waseem; Rabia Ameen; Muhammad Ashraf (Acta Physiologiae Plantarum, 2016)

Prevalence and distribution of human Plasmodium infection in Federally Administrative Tribal Areas of Pakistan - Irfan Hussain; Naveeda Akhtar Qureshi; Muhammad Afzal; Nargis Shaheen; Abid Ali; Asma Ashraf (Acta Parasitologica, 2016)
About 3.6 million Pashtun and over 1.5 million immigrants from Afghanistan live in the federally administered tribal areas (FATA) on the border between Pakistan’s Khyber Pakhtunkhwa Province and southern Afghanistan. Although malaria cases are common in FATA, no detailed studies have yet been performed to reveal the actual status of malaria in the local population and epidemiological data are insufficient to elucidate the actual incidence. A malariometric survey of 691 patients of all ages and genders in seven agencies (districts) in FATA was carried out in 2013 using whole blood samples. Microscopically confirmed positive species were subjected to nested-PCR for the reconfirmation and detection of four species of